2018
DOI: 10.1186/s12904-018-0285-5
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for early assessment of palliative care in lung cancer patients: a population study using linked health data

Abstract: BackgroundAnalysing linked, routinely collected data may be useful to identify characteristics of patients with suspected lung cancer who could benefit from early assessment for palliative care. The aim of this study was to compare characteristics of newly diagnosed lung cancer patients dying within 30 days of diagnosis (short term survivors) with those surviving more than 30 days. To identify indicators for early palliative care assessment we distinguished between characteristics available at diagnosis (age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
2
6
0
1
Order By: Relevance
“…Factors associated with palliative care referral have been extensively examined in the literature 4,6,13–16,22,23 . Our cohort confirmed the association between age and poorer performance status and both palliative care referral and GOC completion.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Factors associated with palliative care referral have been extensively examined in the literature 4,6,13–16,22,23 . Our cohort confirmed the association between age and poorer performance status and both palliative care referral and GOC completion.…”
Section: Discussionsupporting
confidence: 80%
“…Given the superior survival of patients with a targetable oncogenic driver compared to the remainder of the NSCLC population, 1,3 it is perhaps not surprising that these patients are less commonly referred to palliative care at diagnosis. Other factors known to be associated with palliative care referral, such as comorbidities and emergency department presentations or admissions 23 were not assessed in this small study.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that time since diagnosis is an important factor for quality of EOL care, in line with earlier research [45][46][47]. Kelly et al showed that patients with lung cancer who died within 30 days of diagnosis were more likely to die in hospital compared to long-term survivors [48], and Brooks el al. found a negative association between survival time and in-hospital death, with patients surviving <6 months having the greatest risk [46].…”
Section: Plos Onesupporting
confidence: 75%
“…Key characteristics of the datasets are described in Table 2 . Based on our experience using cancer registry data linked to death certificate data and hospital episode data 36 , 37 we focus on these three datasets initially outlining their strengths and weaknesses for PEoLC research and then briefly describe the others.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using cancer registry data linked to hospital episode data for PEoLC research have been published in Ireland. One study examined the palliative care needs of lung cancer patients 36 and a second evaluated the receipt of specialist palliative cancer care in acute hospitals 37 . A feature of these studies is careful study design driven by background knowledge of the data available.…”
Section: Discussionmentioning
confidence: 99%